An Electrically Conducting Three-Dimensional Iron-Catecholate Porous Framework - Mahringer, Andre; Doeblinger, Markus; Hennemann, Matthias; Gruber, Christoph; Fehn, Dominik; Scheurle, Patricia I.; Hosseini, Pouya; Santourian, Irina; Schirmacher, Alfred; Rotter, Julian M.; Wittstock, Gunther; Meyer, Karsten; et al. (Angewandte Chemie International Edition, 2021)
We report the synthesis of a unique cubic metal-organic framework (MOF), Fe-HHTP-MOF, comprising hexahydroxytriphenylene (HHTP) supertetrahedral units and Fe-III ions, arranged in a diamond topology. The MOF is synthesized under solvothermal conditions, yielding a highly crystalline, deep black powder, with crystallites of 300-500 nm size and tetrahedral morphology. Nitrogen sorption analysis indicates a highly porous material with a surface area exceeding 1400 m(2) g(-1). Furthermore, Fe-HHTP-MOF shows broadband absorption from 475 up to 1900 nm with excellent absorption capability of 98.5 % of the incoming light over the visible spectral region. Electrical conductivity measurements of pressed pellets reveal a high intrinsic electrical conductivity of up to 10(-3) S cm(-1). Quantum mechanical calculations predict Fe-HHTP-MOF to be an efficient electron conductor, exhibiting continuous charge-carrier pathways throughout the structure.
CRIS-Team WoS Importer:2021-07-16